Proceedings of the 2016 ACM International Symposium on Wearable Computers 2016
DOI: 10.1145/2971763.2971788
|View full text |Cite
|
Sign up to set email alerts
|

Creating collar-sensed motion gestures for dog-human communication in service applications

Abstract: Working dogs are dogs with one or more specific skills that enable them to perform essential tasks for humans. In this paper we examined motion gestures that working dogs could use to unambiguously communicate with their human companions. We analyzed these gestures in terms of true positives and propensity for false positives by comparing their dynamic time warping distances against a set of everyday gesture libraries (EGL) representing their daily movements. We found four gestures that could be concretely def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In addition, they have also considered to mediate this communication by recognizing motion-based dog gestures-sit, spin, roll, jump, etc.-using a three-axis accelerometer attached to the front of a service dog harness [82]. More recently, they have studied the use of a dog collar with an accelerometer and gyroscope for the recognition of head gestures on dogs [35,83]. Whilst they struggled with the sensitivity of such devices, the researchers did find that gesture recognition through collars was viable and they pointed to looking to how a dog was trained (i.e., with a leash) to give an indication of gestures that could be instantiated in such systems.…”
Section: Haptic and Wearable Technologiesmentioning
confidence: 99%
“…In addition, they have also considered to mediate this communication by recognizing motion-based dog gestures-sit, spin, roll, jump, etc.-using a three-axis accelerometer attached to the front of a service dog harness [82]. More recently, they have studied the use of a dog collar with an accelerometer and gyroscope for the recognition of head gestures on dogs [35,83]. Whilst they struggled with the sensitivity of such devices, the researchers did find that gesture recognition through collars was viable and they pointed to looking to how a dog was trained (i.e., with a leash) to give an indication of gestures that could be instantiated in such systems.…”
Section: Haptic and Wearable Technologiesmentioning
confidence: 99%
“…This meant adding context and societal implications that we see in papers [2,4,9]. This also meant replacing the dimension of Normative Writing with the dimension of Normative Documentation to add more space for prototypes [4,14,19]. The pilot revealed that in many of the ISWC publications we see a prototype that is being used as a form of research archetype [14].…”
Section: Refining the Classification Schemementioning
confidence: 99%
“…All research that takes place in an artificial environment setting is qualified as lab experiment in the scheme of [19]. Typically, researchers use lab experiments to perform limit the influence of contextual factors upon the studied phenomena.…”
Section: Lab Experimentsmentioning
confidence: 99%
“…SaR dogs are important assets in the hands of first responders due to their inherent talents with olfactory and auditory senses. However, in some cases the dog handler is impossible to be present in the same spot with the SaR dog, and thus, a life-critical amount of time is spent as the dog must return to the trainer and guide him to the victim [7].…”
Section: Introductionmentioning
confidence: 99%